Cognitive support through students’ first language in English language learning: Delving into the experiences of teachers from Nepal - Luitel, Binod (Chaitanya Research Journal, 2024)
Use of learner’s first language (L1) in second/foreign language (L2) learning has been a perennial concern for language pedagogues. This research-based deliberation will contribute to the discourse associated with this issue – which is related to the process of navigating learners on their language learning route. The research had the aim of studying how teachers use students’ L1 (Nepali) in teaching English as an L2, and how they justify it. The exploration was made using the data collected from the experiences of 3 teachers working in 3 different schools of rural location in Nepal. Teachers’ written descriptions and interviews were used as data collection techniques. Then data were analyzed thematically with contextual interpretation. Teachers were found employing the students’ (and also the teachers’ own) L1 resource quite a lot in teaching various aspects of English including the subject matter found in the texts, cultural notions, word-meanings, grammatical conceptualization & clarification, teaching story and poetry. As they emphasize, such a use has been a compulsion in favour of students’ learning facilitation – due to the students’ poor level of competence in English. The study has re-established the reality that learners’ L1 does play the role of cognitive bridging in English language learning when the target language is taught to the students having a “poor English base”, and when both the teacher and the students share a common L1.